1988
DOI: 10.2170/jjphysiol.38.361
|View full text |Cite
|
Sign up to set email alerts
|

The functional characteristics of tendon blood circulation in the rabbit hindlimbs.

Abstract: Neurohormonal, mechanical, and muscle exercise effects on tendon blood flow were studied in thirty-five rabbits. After anesthesia by urethane, experiments were performed on in situ preparation of the hindlimb under stable state in systemic blood pressure. Tendon and muscle blood flow were measured simultaneously by the hydrogen gas clearance method, and their temperature and Po t were continuously observed by thermocouple and oxygen sensor, respectively. The resting blood flow in the denervated tendon tibialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Hypoxia may also induce apoptosis through other pathways; for example, one report suggested that hypoxia-induced apoptosis requires the development of acidosis [36], but in our experiments apoptosis occurred with no change in the pH of the medium. In vivo, tendons undergo mechanical strain, and static tension held over several minutes reduces tendon oxygen levels [41]. It is unlikely that tension-induced hypoxia would induce apoptosis in tendons, as periods of complete hypoxia (anoxia) >24 h were required to induce substantial amounts of apoptosis 'in the current study.…”
mentioning
confidence: 59%
“…Hypoxia may also induce apoptosis through other pathways; for example, one report suggested that hypoxia-induced apoptosis requires the development of acidosis [36], but in our experiments apoptosis occurred with no change in the pH of the medium. In vivo, tendons undergo mechanical strain, and static tension held over several minutes reduces tendon oxygen levels [41]. It is unlikely that tension-induced hypoxia would induce apoptosis in tendons, as periods of complete hypoxia (anoxia) >24 h were required to induce substantial amounts of apoptosis 'in the current study.…”
mentioning
confidence: 59%
“…Therefore, application of these findings to the pathogenesis of carpal tunnel syndrome may be limited. However, the relevance of testing the low oxygen levels was demonstrated by Takemiya and Maeda [28]. Using an oxygen electrode, in vivo recordings from the rabbit Achilles tendon revealed PO, levels of 4.1 f 2.0 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, estimations of blood flow for muscle at rest suggested that approximately half of the total flow was nutritive and thus capable of clearing intramuscular injected markers (17). More recent estimates suggest this proportion may be even lower (16,36).…”
mentioning
confidence: 95%